Características quantitativas da carcaça e físico-químicas da carne de cordeiros Santa Inês abatidos com três espessuras de gordura subcutânea - Andrade, Ana Carla Santana (2014)
This study aimed to evaluate the quantitative carcass traits and physicochemical meat of Santa Inês lambs slaughtered at 2.0; 3.0 and 4.0 mm of backfat thickness, assessed by ultrasound in Longissimus dorsi.Twenty-four lambs, male, unneutered, with approximately 100 days of age and live weight of 22.7 ± 3.75 kg were used. The experimental design was completely randomized design with three treatments and eight replications.Lambs were confined, fed pelleted complete ration designed to gain 0.300 kg / day. Assessments by ultrasound in Longissimus dorsi between the 12th and 13th ribs and weighed every 14 days were performed.Lambs as they reaching the predetermined thickness of fat were slaughtered. The right half carcasses were five commercial cuts: neck, shoulder, ribs, loin and leg. The cuts were dissected into subcutaneous and intermuscular fat, muscle, bones and waste.Significant differences (P <0.05) on the weight of the shoulder and leg, with the highest average obtained by lambs slaughtered at 4.0 mm of fat thickness were observed.There was no effect of fat thickness for dressing of cuts. The percentages of retail cuts of muscles did not differ (P> 0.05) between treatments. Lambs slaughtered at 3.0 and 4.0 mm differed (P <0.05) for the percentage of total fat in the palette.Lambs slaughtered at 2.0 mm showed a higher percentage of bone in loin. The leg muscularity lambs slaughtered at 2.0 mm was lower (0.34) compared to that of lambs slaughtered at 3.0 and 4.0 mm of fat thickness. No difference (P> 0.05) was observed in muscle: bone and muscle: fat between treatments. Samples of Longissimus dorsi muscle were used for physical and chemical characteristics. The initial pH (pH0h) did not differ (P> 0.05) between treatments, with average value of 6.24. For the pH measured at 24 hours after slaughter (pH24h), differences (P <0.05) were observed for the treatment with 4.0 mm thickness of subcutaneous fat. Meat of lambs slaughtered at 3.0 and 4.0 mm thick fat had higher lightness (L *). The softness (2.21 kgf / cm 2) and weight loss by cooking (13.90%) of meat were not affected by the thickness of subcutaneous fat. No significant differences (P> 0.05) for moisture content (74.39%) and crude protein (22.10%) were observed.For contents of total lipids of the flesh significant differences (P <0.05) were observed between lambs slaughtered at 2.0 mm and lambs with 3.0 and 4.0 mm thickness of subcutaneous fat. The regional composition of the carcass and tissue cuts, as well as the rate of muscle were influenced by the thickness of subcutaneous fat.Physical and chemical characteristics of meat from Santa Ines lambs were changed, however, remained in the range considered acceptable for sheep meat. Is recommended to the slaughter of lambs with 3.0 mm thick subcutaneous fat remained for 33 days unless and similar weight to lambs slaughtered at 4.0 mm thick subcutaneous fat.